KONTRIBUSI INTERAKSI TEMAN SEBAYA TERHADAP KEMANDIRIAN SISWA DALAM PEMILIHAN JURUSAN - Sandika, Nanang Aria (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2024)
This research aims to find out the extent of peer interaction involvement in students' independence in choosing a major. Because many students experience difficulties such as not being able to determine their major. This research is quantitative research with descriptive correlation methods. The population of this research was 384 people and took a sample of 196 students. Based on the analysis, it is known that peer interaction is high, reaching 80%. Furthermore, the results of data analysis on student independence in choosing a major were categorized as independent (high) with a percentage of 80%. After conducting a regression analysis, it was discovered that peer interaction contributed to student independence in choosing a major (20.6%). It can be interpreted that peer interaction contributes to making students independent in determining the choice of major they will pursue. The results of this research can be a reference or consideration for students.